Efek Sinergis Alumina Trihydrate Dan Melamine Cyanurate Terhadap Ketahanan Api Glass Fiber Reinforced Polymer (GFRP) - Ridha Inayah; Wiwik Dwi Pratiwi; Rizal Indrawan (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Glass Fiber Reinforced Polymer (GFRP) in train interior components must have good fire resistance properties. Therefore, it is necessary to add a flame retardant compound to the GFRP material. In this study, Alumina Trihydrate (ATH) and Melamine Cyanurate (MCA) were mixed into a vinyl ester resin. The method of making GFRP refractory specimens uses the hand lay-up method. GFRP is mixed and tested for fire resistance standard ORE B 106.2. The results obtained after the addition of 25% ATH, a mixture of 25% ATH with 5% MCA, 10% MCA with 25% ATH, and 15% MCA with 25% ATH, 25% ATH in the outer layer, and a mixture of 5% MCA with 25% ATH in the outer layer of the resin weight is able to increase fire resistance. Optimum GFRP fire resistance at the addition of 25% ATH to the weight of the resin in the outer layer. The result of the burned area is 84.84 cm² with a fire extinguishing time of 0.33 seconds after the fire source leaves the specimen. The results show that the mixture of ATH and MCA has a synergistic effect on fire resistance properties, so it becomes a recommendation for interior sidewall panels and ceiling panels on trains according to the ORE B 106.2 standard